Example comparisons of type E (4.1), C (4.2), F (4.3), and T (4.4.). - Audra E. Ames (11349386); Susanna B. Blackwell (10013873); Outi M. Tervo (10013864); Mads Peter Heide-Jørgensen (7869812) (2021)
Spectrogram parameters: DFT size 512, 256 sample hop size, and Hann window 512 samples.